Comparison of Surgical Methods for the Correction of Low Amounts of Corneal Astigmatism during Cataract Surgery - Schallhorn, Steven C.; Schallhorn, Julie M. (Ophthalmology (Rochester, Minn.), 2025)
To compare the methods of corneal astigmatism management during intraocular surgery in eyes with low corneal astigmatism. Retrospective study. Patients undergoing cataract or refractive lens exchange surgery with data recorded in a cloud-based surgical planner (Veracity; Zeiss) with preoperative corneal astigmatism of between 0.75 and 1.50 diopters (D). Eyes were divided into 3 groups: eyes with implantation of a toric intraocular lens (IOL; the toric group), eyes with nontoric IOLs that underwent limbal relaxing incisions (LRIs) or astigmatic keratotomy (AK; the LRI or AK group), and the uncorrected group, which comprised eyes with nontoric IOLs that did not receive any intentional corneal astigmatism correction. Data were stratified further according to the magnitude of preoperative corneal astigmatism into 3 categories: 0.75 D or more to less than 1.00 D, 1.00 D or more to less than 1.25 D, and 1.25 D or more to 1.50 D or less. A multivariable model was used to assess the effect of the procedure type on outcomes. Percentage of eyes achieving 0.50 D or less residual manifest astigmatism and odds ratios for the likelihood of not achieving 0.50 D or less manifest astigmatism. The study included 40 289 eyes (toric group, 10 100 eyes; LRI or AK group, 5811 eyes; uncorrected group, 24 378 eyes). In the group of eyes with preoperative astigmatism of 0.75 D or more to less than 1.00 D, compared with toric IOLs, the odds of not achieving 0.50 D or less manifest astigmatism increased 2.83-fold in the LRK or AK group and 5.72-fold in the uncorrected group. For corneal astigmatism of 1.00 D or more to less than 1.25 D, the odds increased 3.9-fold with LRI or AK and 7.64-fold in eyes with uncorrected astigmatism. In the eyes with 1.25 D or more to 1.50 D or less of corneal astigmatism, the odds increased 4.70-fold and 10.27-fold for the LRI or AK group and uncorrected group, respectively. The presence of against-the-rule astigmatism considerably increased the odds of not achieving 0.50 D or less manifest astigmatism, mainly in the eyes with uncorrected astigmatism. The toric IOL group showed the most accurate and consistent astigmatism correction, regardless of the magnitude of preoperative corneal astigmatism or axis orientation. Proprietary or commercial disclosure may be found in the Footnotes and Disclosures at the end of this article.